STRATEGI PROMOSI MENINGKATKAN SALES DAN BRAND AWARENESS UKM X TERHADAP MINAT BELI KONSUMEN PADA MEDIA SOSIAL TIKTOK SHOP - Osel, Jefferson (Seminar Nasional Ilmu Terapan, 2024)
The development of the times from year to year affects daily life and activities. This development has triggered the use of gadgets by using social media as a daily activity, including in the business sector. In this article entitled "Promotional Strategies to Increase Sales and Brand Awareness of UKM The research method used is qualitative. The sample used for this research consisted of six people who were divided into the UKM @Eightyninesneaks group and the customer group. The data analysis technique used is data triangulation. The results and discussion show that the promotional strategy used needs to be improved in creating varied video content, approaching consumers, and conducting Tiktok ads in order to increase account engagement on the Tiktok Shop social media. This strategy is a reference for increasing sales and brand awareness of consumer buying interest.